2015
DOI: 10.1371/journal.pntd.0003398
|View full text |Cite
|
Sign up to set email alerts
|

Using Modelling to Disentangle the Relative Contributions of Zoonotic and Anthroponotic Transmission: The Case of Lassa Fever

Abstract: BackgroundZoonotic infections, which transmit from animals to humans, form the majority of new human pathogens. Following zoonotic transmission, the pathogen may already have, or may acquire, the ability to transmit from human to human. With infections such as Lassa fever (LF), an often fatal, rodent-borne, hemorrhagic fever common in areas of West Africa, rodent-to-rodent, rodent-to-human, human-to-human and even human-to-rodent transmission patterns are possible. Indeed, large hospital-related outbreaks have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
104
2
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(120 citation statements)
references
References 48 publications
(93 reference statements)
2
104
2
2
Order By: Relevance
“…Combined with the intermingling of human and M. natalensis samples on the phylogenetic tree (Figure 2A), this is consistent with a genetically diverse pool of LASV being maintained in its rodent reservoir, with most human infections caused by genetically distinct viruses. A recent study suggested that human-to-human transmission of LASV may account for up to 20% of all cases (Lo Iacono et al, 2015), but we found little support for this in our dataset. This does not rule out human-to-human transmission entirely, but it suggests that human transmission chains are the exception rather than the rule.…”
Section: Discussioncontrasting
confidence: 98%
See 2 more Smart Citations
“…Combined with the intermingling of human and M. natalensis samples on the phylogenetic tree (Figure 2A), this is consistent with a genetically diverse pool of LASV being maintained in its rodent reservoir, with most human infections caused by genetically distinct viruses. A recent study suggested that human-to-human transmission of LASV may account for up to 20% of all cases (Lo Iacono et al, 2015), but we found little support for this in our dataset. This does not rule out human-to-human transmission entirely, but it suggests that human transmission chains are the exception rather than the rule.…”
Section: Discussioncontrasting
confidence: 98%
“…Similarly, it has been suggested that up to 20% of LF cases also arise from human-to-human transmissions (Lo Iacono et al, 2015). Sustained human-to-human transmission should result in a ‘ladder-like’ structure of the phylogenetic tree along with a strong correlation between a sample's collection date and its genetic distance from the root of the tree over a short time period.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This puts the health workers, their families and the wider community at risk of secondary infections, inundation, other study also revealed significant knowledge gaps concerning LF among primary care providers in a LF endemic suburban community Andrew et al [22].…”
Section: Discussionmentioning
confidence: 93%
“…In addition, similar to minority clusters transmitting strain of higher virulence, increased viral loads in a minority subset of infected individuals would not necessarily result in an observable change in overall case-fatality rates. The concept of disease super spreaders had been hypothesized during past outbreaks with EBOV and with other pathogens [27][28][29][30] and is consistent with observations during the current outbreak, in which a traditional healer was shown to have directly infected 13 others after dying of EVD [20] and was eventually linked to >300 EBOV cases [31]. A recent study also reported several chains of EBOV transmissions in Guinea, showing how a small number of infected individuals can transmit the virus to a larger number of people and drive the overall spread of EBOV in the community, as opposed to the majority of patients, who infect few others [32].…”
Section: Discussionmentioning
confidence: 99%